Biosafety to Reduce Industrial Worker Illnesses Caused by Exposure to Antioxidants in Fish Meal (LACCEI, 2024)
The objective of this study is to use biosafety to reduce illnesses in packing personnel caused by exposure to antioxidants in fish meal in an industrial plant. The work was carried out in the packing area of Hayduk S. A. in Chincha, Peru. A pre-experimental study was carried out using biosafety as a stimulus. Using the SPSS version 22 program, surveys, pre- and post-tests were carried out, and with the data collected, the standard deviation, normality tests and the t-student test were calculated. The following conclusions were drawn: In the pre-test, 100% of the workers had no knowledge of biosafety, did not know how to react in occupational accidents and did not understand the meaning of the Occupational Medical Evaluation (OME). However, after the training, workers demonstrated a thorough knowledge of the subject and were fully aware of the need to take precautions in case of occupational accidents, among other things. R is -0.872 for the linear correlation. This shows that there is a strong correlation between the observed data of positive changes in worker behavior, commitment and knowledge about biosafety, resulting in disease mitigation. This is an inverse, moderate, negative correlation. It is advisable to maintain scheduled training on biosafety and occupational health issues.